2015
DOI: 10.1007/s00253-015-6617-y
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the effects of arginine and lysine on a monoclonal antibody C-terminal lysine variation in CHO cell cultures

Abstract: C-terminal lysine variants are commonly observed in monoclonal antibodies (mAbs) and found sensitive to process conditions, especially specific components in culture medium. The potential roles of media arginine (Arg) and lysine (Lys) in mAb heavy chain C-terminal lysine processing were investigated by monitoring the lysine variant levels under various Arg and Lys concentrations. Both Arg and Lys were found to significantly affect lysine variant level. Specifically, lysine variant level increased from 18.7 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…In our previous study, carboxypeptidase B and carboxypeptidase H have been confirmed as two major basic carboxypeptidases responsible for C-terminal lysine cleavage in CHO cells (Zhang et al 2015). GAPDH, which was used as an internal control, was reported not to be affected by culture temperature (Mason et al 2014).…”
Section: Resultsmentioning
confidence: 98%
“…In our previous study, carboxypeptidase B and carboxypeptidase H have been confirmed as two major basic carboxypeptidases responsible for C-terminal lysine cleavage in CHO cells (Zhang et al 2015). GAPDH, which was used as an internal control, was reported not to be affected by culture temperature (Mason et al 2014).…”
Section: Resultsmentioning
confidence: 98%
“…High concentrations of lysine and histidine have also been shown to slightly reduce cellular growth rate in the exponential phase while improving cell viability in the late stage of a production process . However, high concentration of lysine may have an inhibitory effect on basic carboxypeptidases, resulting in an increase in C‐terminal lysine variants . Therefore, the concentration of lysine and histidine may be changed based on specific product requirements.…”
Section: Key Components Of Mammalian Cell Culture Mediamentioning
confidence: 99%
“…However, unlike lysine, high arginine concentrations can inhibit cell growth and reduce viability . Additionally, a rise in arginine concentration has been shown to double the amount of C‐terminal lysine variant and thereby increase the heterogeneity of an antibody product …”
Section: Key Components Of Mammalian Cell Culture Mediamentioning
confidence: 99%
See 2 more Smart Citations